Participatory impact pathways analysis: a practical application of program theory in research-for-development - Douthwaite, Boru; Álvarez, S.; Cook, Simon E.; Davies, R.; George, Pamela; Howell, J.; Mackay, R.; Rubiano, J. (2007)
The Challenge Program on Water and Food pursues food security and poverty alleviation through the efforts of some 50 researchfor-evelopment projects. These involve almost 200 organizations working in nine river basins around the world. An approach was developed to enhance the developmental impact of the program through better impact assessment, to provide a framework for monitoring and evaluation, to permit stakeholders to derive strategic and programmatic lessons for future initiatives, and to provide information that can be used to inform public awareness efforts. The approach makes explicit a project's program theory by describing its impact pathways in terms of a logic model and network maps. A narrative combines the logic model and the network maps into a single explanatory account and adds to overall plausibility by explaining the steps in the logic model and the key risks and assumptions. Participatory Impact Pathways Analysis is based on concepts related to program theory drawn from the fi elds of evaluation, organizational learning, and social network analysis.